The Role of Play Methods in Developing Creativity in Early Childhood - Siti Khodijah; Cindy Atika Rizki (Jurnal Pendidikan Anak Usia Dini, 2025)
This study aims to examine the role of play methods in developing early childhood creativity. Play is not only a form of entertainment but also an effective learning medium to stimulate imagination, problem-solving, and children’s social skills. Using a qualitative approach through a literature review, this study found that play methods significantly contribute to children’s creativity development across cognitive, affective, and psychomotor domains. The results emphasize that play methods should be integrated into early childhood education to optimize their creative potential.